Exploring Operations and Talent Management Challenges of FM Radio in India - Vilasrao Ingle, Shamal (Digital Repository of Theses, 2026)
My original contribution to knowledge is a meticulous, grounded exploration of the challenges in operational and talent management front in the FM Radio Industry in India as it sails into digitalisation. While much of the discourse on radio’s decline focuses on external factors like the evolution of audio-visual media, competition from streaming platforms, shifting audience preferences, and declining attention span, this study also gives an insight into the internal challenges that continuously shape the industry’s course but often remain unaddressed. The purpose of this research is to find solutions to long-standing, disregarded yet implicit issues, on the verge of raising new issues as the industry sets foot in the digital avatar without losing its soul. The challenges facing FM radio are not completely technological or market-driven, but are deeply rooted in organizational practices, internal advertising rate war, talent management, adaptation to media convergence, implementation and government policies. The study highlights the cultural significance of radio in India. This enduring relationship, also a strong point, can conceal the urgent need for modernization and modification of the medium. The researcher used an exploratory design of research and with a grounded research methodology, interviewing FM Radio professionals, the outcome reveals the internal realities tackled by FM Radio’s programming personnel. This study discloses internal issues of the industry, such as a lack of structured training and upskilling for radio talent in digital competencies, the daily time management tussles of production and sales team to crack a client, the substandard willpower of the Association of Radio Operators for India (AROI) to seek help from the government bodies such as MIB concerned with solving existing business problems of insufficient revenue generation or to offer a sustainable solution. Altogether limiting innovation, obstructing local connection of radio, constraining career development, and ultimately reducing the industry’s capacity to compete with the agile digitalised media market, and other mainstream media giants in its full potential. Radio is a free medium, and it should remain so for the masses. In conclusion, AROI should consider proposing and following up strongly with MIB to urgently come up with sustainable business solutions and relax heavy guidelines. Whereas the FM Radio operators need to rethink where they are heading the industry, and make sure they are prepared with a foolproof foundation first.